Global Alfvén eigenmodes in the H-1 heliac - Hole, M J; Blackwell, B D; Bowden, G; Cole, M; Könies, A; Michael, C; Zhao, F; Haskey, S R (Plasma physics and controlled fusion, 2017)
Recent upgrades in H-1 power supplies have enabled the operation of the H-1 experiment at higher heating powers than previously attainable. A heating power scan in mixed hydrogen/helium plasmas reveals a change in mode activity with increasing heating power. At low power ( < 50 kW) modes with beta-induced Alfvén eigenmode frequency scaling are observed. At higher power modes consistent with an analysis of nonconventional global Alfvén eigenmodes (GAEs) are observed, the subject of this work. We have computed the mode continuum, and identified GAE structures using the ideal MHD solver CKA and the gyrokinetic code EUTERPE. An analytic model for ICRH-heated minority ions is used to estimate the fast ion temperature from the hydrogen species. Linear growth rate scans using a local flux surface stability calculation, LGRO, are performed. These studies demonstrate drive from the radial spatial gradient of circulating particles whose speed is significantly less than the Alfvén speed, and are resonant with the mode through harmonics of the Fourier decomposition of the strongly shaped heliac magnetic field. They reveal drive is possible with a small ( n f n 0 < 0.2 ) hot energetic tail of the hydrogen species, for which T f > 300 eV . Local linear growth rate scans are also complemented with global calculations from CKA and EUTERPE. These qualitatively confirm the findings from the LGRO study, and show that the inclusion of finite Larmor radius effects can reduce the growth rate by a factor of up to ten, and increases the marginal stability fast ion temperature by a factor of two. Finally, a study of damping of the global mode with the thermal plasma is conducted, computing continuum damping , and the damping arising from finite Larmor radius and parallel electric fields (via resistivity). We find that continuum damping is of order 0.1% for the configuration studied. A similar calculation in the cylindrical plasma model produces a frequency 35% higher and a damping 30% of the three-dimensional result: this confirms the importance of strong magnetic shaping to the frequency and damping. The inclusion of resistivity lifts the damping to γ = − 0.189 . Such large damping is consistent with experimental observations that in absence of drive the mode decays rapidly (∼0.1 ms).